Predictor Variables Affecting Coffee Shop Performance in Tangerang - Pangguna, Wihanry; Christian, Michael; Indriyarti, Eko Retno (Universitas Bunda Mulia, 2024)
The objective of this study is to ascertain the impact of market orientation, technological orientation, and entrepreneurial orientation on the success of coffee shop enterprises. This study employs a quantitative methodology, utilizing a sample size of 135 coffee shop owners in Tangerang. The sample approach employed was purposive sampling. Analysed data was processed with the SmartPLS 4.0 analysis tool. The findings of the hypothesis testing demonstrate that market orientation has a significant impact on business performance. Market orientation promotes a shift in entrepreneurs' mindset, encouraging them to adopt the consumer's point of view. This enables entrepreneurs to gain insights into consumer demands by studying information gathered from consumers and the market on products that are favored by consumers. This notion will enhance the reception of items among consumers, leading to beneficial outcomes for the corporation in terms of improved business performance. Entrepreneurial orientation is another factor that has a major impact on business performance, and it can potentially account for similar findings. Entrepreneurial orientation fosters a mindset among business individuals that promotes the implementation of daring and aggressive business tactics, as well as innovation. This mindset enhances the business owner's confidence in achieving their goals and ultimately leads to improved business performance. Business professionals can implement market orientation and entrepreneurial orientation, both of which have demonstrated their effectiveness. Enhance operational efficiency and optimize business outcomes. Entrepreneurs participate in specialized training programs to enhance the sophistication and competitive edge of their coffee shop business units. Further investigation might be carried out in alternative industries outside from the coffee shop industry to obtain a wider range of outcomes.